Reforming Chile : cultural politics, nationalism, and the rise of the middle class - Barr-Melej, Patrick (University of North Carolina Press, 2001)
Highlighting the crucial yet largely overlooked role played by society's middle layers in the historical development of Latin America, Patrick Barr-Melej provides the first comprehensive analysis of the rise of Chile's middle-class reform movement and its profound impact on that country's cultural and political landscapes. He shows how a diverse collection of middle-class intellectuals, writers, politicians, educators, and bureaucrats forged a "progressive" nationalism and advanced an ambitious cultural-political project between the 1890s and 1940s. Together, reformers challenged the power of elite groups and sought to quell working-class revolutionary activism as they endeavored to democratize culture and fortify liberal democracy. Using sources that range from archival documents and newspapers to short stories, novels, and school textbooks, Barr-Melej examines the reform movement's cultural ideas and their political applications, especially as they were articulated in the areas of literature and public education. In the process, he provides a new framework for understanding Chile's cultural and political evolution, as well as the complicated place of the middle class in a society experiencing the swift changes inherent in capitalist modernization